2018
DOI: 10.3390/cells7070066
|View full text |Cite
|
Sign up to set email alerts
|

The Desmosomal Cadherin Desmoglein-2 Experiences Mechanical Tension as Demonstrated by a FRET-Based Tension Biosensor Expressed in Living Cells

Abstract: Cell-cell junctions are critical structures in a number of tissues for mechanically coupling cells together, cell-to-cell signaling, and establishing a barrier. In many tissues, desmosomes are an important component of cell-cell junctions. Loss or impairment of desmosomes presents with clinical phenotypes in the heart and skin as cardiac arrhythmias and skin blistering, respectively. Because heart and skin are tissues that are subject to large mechanical stresses, we hypothesized that desmosomes, similar to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
5
23
0
Order By: Relevance
“…Notably, two independent reports recently demonstrated that the desmosomal proteins, Dsg2 and Dp function as the biosensor in human cardiomyocytes and canine kidney simple epithelial cells [3,40]. These findings, along with the current study, collectively underscore the importance of desmosomes as mechanosensory and load-bearing structures that coordinate with AJs in control of tissue integrity and homeostasis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Notably, two independent reports recently demonstrated that the desmosomal proteins, Dsg2 and Dp function as the biosensor in human cardiomyocytes and canine kidney simple epithelial cells [3,40]. These findings, along with the current study, collectively underscore the importance of desmosomes as mechanosensory and load-bearing structures that coordinate with AJs in control of tissue integrity and homeostasis.…”
Section: Discussionsupporting
confidence: 79%
“…The importance of desmosomal cadherins, as well as other DSM constitutive proteins, in tissue homeostasis and physiological function, has been underscored by various vesiculobullous diseases with clinical manifestation of blistering and fragility syndrome of skin and oral mucosa as well as heart failure in some cases [10,52]. Recent studies have uncovered that two DSM proteins, Dsg2 and Dp, are capable of sensing external mechanical loading, highlighting the probable involvement of DSM proteins in mechanobiology [3,40].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of desmosomal cadherins, as well as other DSM constitutive proteins, in tissue homeostasis and physiological functions, has been underscored by various vesiculobullous diseases with a clinical manifestation of blistering and fragility syndrome of skin and oral mucosa, as well as heart failure in some cases [14,15]. Recent studies have uncovered that two DSM proteins, desmoglein-2 (Dsg2) and desmoplakin (Dp), are capable of sensing external mechanical loading, highlighting the probable involvement of DSM proteins in mechanobiology [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Dsp together with keratins may have a direct role in apical expansion by providing the emerging cells and with the rigidity needed to support apical expansion. Certainly, desmosomes themselves have been shown to provide mechanical strength to cells (Baddam et al, 2018;Puzzi et al, 2018) and keratins convey stiffness to cells important for cell shape changes (Ramms et al, 2013). Dsp and keratin attachment could also be required to provide adequate tension in the field of outer epidermal cells.…”
Section: Dsp Is Required For Morphogenesis Of the Epidermis In X Laevismentioning
confidence: 99%
“…For example, loss of desmoplakin function results in decreased cell forces and stiffness's (Broussard et al, 2017) which could affect cell shape, cell movements as well as mechanotransduction events. Forces across the desmosomal protein desmoglein2, using a tension sensor further suggest that the desmosome is more than a passive rivet like structure (Baddam et al, 2018). While many of the intriguing functions of desmosomes are unfolding in cells cultured in a dish or in other artificial in vitro systems, it is unclear whether all of these functions also widely apply in vivo, especially during embryonic development.…”
Section: Introductionmentioning
confidence: 99%